2020
DOI: 10.1038/s41419-020-2264-z
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of tumor necrosis factor-α determines its protective or damaging effect on liver injury by regulating Yap activity

Abstract: Previous studies have shown that tumor necrosis factor (TNF)-α is a mediator of hepatotoxicity in liver injury. Moreover, TNF-α has also been reported to have a protective effect in liver regeneration, yet the function of TNF-α during liver injury remains controversial. Here, we report that the concentration of TNF-α determines its functions. High concentrations of TNF-α could aggravate LPS-induced liver injury. However, the TNF-α level was unchanged during APAP-induced liver injury, which exerted a protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 47 publications
(50 reference statements)
2
28
0
Order By: Relevance
“…The concentration of TNF-α level in hepatic cells determined its damaging or protective effect on liver injury. Previous study has also shown that TNF-α is involved in regulating proliferation and cell death of hepatocytes ( Zhao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 92%
“…The concentration of TNF-α level in hepatic cells determined its damaging or protective effect on liver injury. Previous study has also shown that TNF-α is involved in regulating proliferation and cell death of hepatocytes ( Zhao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 92%
“…When kupffer cells were depleted or TNF-α was deficient, C14-Tri-LAN-Gly-induced A20 upregulation was impaired. In inflammatory conditions, TNF-α has both a beneficial and a deleterious effect on hepatocytes ( 32 ). TNF-α is a proximal mediator of hepatotoxicity in several models of hepatitis and liver damage including LPS/D-GalN ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNF is a pleiotropic autocrine and paracrine mediator important in multiple signaling cascades that range from activating immune cells to ght viruses, bacteria, and cancer cells, to promoting entry of monocytes and lymphocytes into atherosclerotic lesions [4,105,106]. The latter process is recognized to be pro-atherogenic.…”
Section: Discussionmentioning
confidence: 99%